A Mystery of Academic and Industrial Skill Discordance among Business Graduates in Pakistan - Dr. Naveed Hussain Shah; Dr. Imtiaz Ali Khan; Dr. Burhan Ali Shah; Dr. Faisal Khan (Journal of Business & Tourism, 2021)
The study had explored the cognitive, non-cognitive and vocational skill required by the Pakistani organizations and found that there are various dimension that employer are interested among their potential employee. It was observed that Non cognitive are the more deficient one among the focused and as per gender is concerned their little response as per all skills however on Non-cognitive skills a bet more maturity exist among female candidates whereas the confidence level and lower literacy rate disturb their response on job market. Curriculum covering the Field specific theoretical and practical knowledge there is rare convergence on field specific practical knowledge. The study reveals a higher attention on industry academia collaboration through developing a high level of university-Industry linkages.